2008
DOI: 10.1111/j.1365-2133.2008.08932.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of treatment of nine cases of recalcitrant severe hidradenitis suppurativa with carbon dioxide laser

Abstract: CO2 laser treatment should be considered as a treatment option in recalcitrant HS, where multiple medical treatments have been ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 19 publications
2
47
1
9
Order By: Relevance
“…In the pathogenesis of HS, follicular plugging by keratinized squamous epithelium is believed to be an essential initial step that progresses to secondary infection and the development of abscesses and sinus tracts [12][13][14][15]. The clinical course of this type of disease tends to be chronic and recurrent in a significant portion of cases, despite various pharmacological and surgical treatments [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the pathogenesis of HS, follicular plugging by keratinized squamous epithelium is believed to be an essential initial step that progresses to secondary infection and the development of abscesses and sinus tracts [12][13][14][15]. The clinical course of this type of disease tends to be chronic and recurrent in a significant portion of cases, despite various pharmacological and surgical treatments [16].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical course of this type of disease tends to be chronic and recurrent in a significant portion of cases, despite various pharmacological and surgical treatments [16]. Madan et al [14] suggested that recalcitrant and severe HS could be effectively treated with the CO 2 laser, although scar contracture following CO 2 laser treatment was noted. The advantages of using the CO 2 laser included good hemostasis, excellent visualization of the operative field, and accurate assessment of residual diseased tissue [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven out of the nine patients had complete remission for 12 months or longer after the last laser treatment. Two patients developed axillary scar contracture, but this was not sufficient to limit limb movement [26]. Hazen and Hazen treated 185 areas in 61 patients with the Sharplan CO 2 laser using the excision and marsupialization technique, and left them to heal with secondary intention except in one patient.…”
Section: Lasers and Light-based Therapies Used In The Treatment Of Hsmentioning
confidence: 99%
“…126,127 Long-pulsed neodymium: yttrium-aluminum-garnet laser (Nd:YAG) designed for hair removal, has been tried in the treatment of HS lesions and background skin, based on the assumption that HS starts in the hair follicle. 1 Reported improvement rates range from 31.6% to 72.7%.…”
Section: -Lasers and Lightsmentioning
confidence: 99%